Clay minerals, Sr-Nd isotopes and provenance of sediments in the northwestern South China Sea. (15th October 2020) - Cai, Guanqiang; Li, Shun; Zhao, Li; Zhong, Lifeng; Chen, Hongjun
Graphical abstract: Highlights: Sediments from the shelf and slope of the NW SCS show different clay minerals and Sr-Nd isotopic compositions. Sediments in NW slope are sourced mainly from the Indochina, Hainan Island, and South China. An increase of terrigenous supply possibly from the paleo-Red River drainage basin during last glacial. Abstract: The clay mineralogy and Sr-Nd isotopic composition of sediments collected in the northwestern South China Sea (SCS) were investigated to understand sediment provenance and changes in the SCS since the Late Pleistocene. Our results show that the clay mineral assemblages of the surface sediments are characterized by high amounts of illite and smectite, and low amounts of kaolinite and chlorite. The 87 Sr/ 86 Sr ratios of the surface sediments vary from 0.709617 to 0.734416, and εNd values range from −11.6 to −8.3. The clay minerals and Sr-Nd isotope records suggest that sediments in the northwestern SCS are derived from multiple sources. The sediments deposited in the eastern shelf offshore of Hainan originate predominantly from Hainan Island and South China, whereas sediments in the western shelf offshore of Hainan are derived mainly from Indochina and Hainan Island. However, sediment source and transport mechanisms in the northwestern slope of the SCS are more complicated. Our results suggest that input from the west may be the major sediment source, but regions in the east (Taiwan and Luzon) also contribute part of the terrigenous materials. Downcore variations of Sr-Nd isotopic composition in core sediments show clear glacial–interglacial fluctuations. Higher 87 Sr/ 86 Sr ratios occur during glacial period, indicating that the input of terrigenous materials from old continental rocks becomes one of the important sediment sources during these periods. The exposure of continental shelf and southward migration of the coastline during the glacial sea-level lowstand led to an increase of terrigenous supply to the northwestern slope of the SCS. The paleo-Red River and Indochina are also potentially important contributors.